Variability of chloroplast DNA in the genus Passiflora L - Sánchez, I.; Angel, F.; Grum, M.; Duque E., Myriam Cristina; Lobo Arias, Mario; Tohme, Joseph M.; Roca, W. (Springer, 1999)
Restriction fragment analysis was used to determine the variation of chloroplast DNA (cpDNA) among and within different species of Passiflora. Total DNAs of 35 accessions, representing 12 species, were digested with four restriction endonucleases. Southern blots of the restriction digests were then probed with eight different cpDNA fragments from Petunia and mung bean. Two hundred fragments were scored, and used to estimate the genetic distance among the species according to UPGMA (Unweighted Pair Group Method using Aritmetic Averages) analysis. Overall, the analysis successfully separated species according to the present classification scheme based on morphological description demonstrating profound cpDNA diversity among the 12 species evaluated. Intraspecific variation was observed in four of seven species that were represented by more than two accessions.